Task effects in the mid-fusiform gyrus: A comparison of orthographic, phonological, and semantic processing of Chinese characters - Guo, Yi; Burgund, E. Darcy (Brain and language, 2010)
The left mid-fusiform gyrus is repeatedly reported to be involved in visual word processing. Nevertheless, it is controversial whether this area responds to orthographic processing of reading. To examine this idea, neural activity was measured using functional magnetic resonance imaging in the present study while subjects performed phonological, semantic, and orthographic tasks with Chinese characters under equivalent task difficulties. One region in the left mid-fusiform gyrus exhibited greater activity during the orthographic task than during the phonological and semantic tasks, which did not differ, suggesting that this region is involved in orthographic processing to a greater extent than phonological or semantic processing. In addition, a region in the right mid-fusiform gyrus exhibited a similar effect. This right mid-fusiform activity may relate to the use of pictorial Chinese characters.